Urban accupuncture: Architecture as a catalyst for environmental and water conservation in the context of the Kilimanjaro Informal Settlement - Main, Kenneth (School of Architecture, Planning and Geomatics, 2017)
The following dissertation will attempt to establish an approach to dealing with the issue of waste contamination and water conservation in the natural and urban landscapes of the riverbed, its rivers' edges and its man-made peripheries. This research locates itself at the northern boundary of the city of Windhoek along a stretch of polluted riverbed in the Kilimanjaro Informal Settlement (KIS) where public environments are undefined, unhealthy and in many ways disconnected from the greater metropolitan areas. In the creation of an architectural approach 'urban acupuncture' will be explored in an attempt to create Architecture that has the potential to influence areas beyond its physical boundaries and which can re-establish and re-imagine the value of the river for its unseen influence in shaping the city as rapid urbanisation is taking place. In this section of the city, particular aspects of environmental degradation, water conservation and lack of basic infrastructure form a basis of inquiry to which an urban framework has been proposed. Drawing on theories of landscape urbanism, this urban framework acts to establish an alternative and more efficient infrastructural system which collects, stores, recycles and reuses wastewater for both drinking and irrigation purposes. Seen as the bi-product of this urban framework, the KIS Agricultural Learning Centre has been proposed which provides the necessary link between this infrastructural insertion and both the public and social constructs of the Kilimanjaro Informal Settlement.